Spectroscopic properties of protochlorophyllide analyzed in situ in the course of etiolation and in illuminated leaves - Schoefs, B; Bertrand, M; Franck, F (Photochemistry and photobiology, 2000)
The spectroscopic properties of photoactive (i.e. flash-transformable) and nonphotoactive protochlorophyll(ide)s (Pchl(ide)) were reinvestigated during the development of bean leaves in darkness. Two phases in the process of Pchl(ide) accumulation were apparent from quantitative measurements of pigment content: a lag phase (first week) during which photoactive Pchl(ide) accumulated faster than nonphotoactive Pchl(ide); and a fast phase (second week), showing parallel accumulation of both types of Pchl(ide). 'Flashed-minus-dark' absorbance difference spectra recorded in situ at 77 K showed that P650-655 was the predominant form of photoactive protochlorophyllide regardless of developmental stage. Quantitative analysis of energy migration processes between the Pchl(ide) forms showed the existence of energy transfer units containing a 1:8 ratio of nonphotoactive and photoactive Pchl(ide)s during development. Gaussian deconvolution of in situ 77 K fluorescence spectra indicated that the 633 nm band of nonphotoactive Pchl(ide) was made of four bands, at 625, 631, 637 and 643 nm, whose relative amplitudes only slightly changed during development. The emission band of photoactive Pchlide was also analyzed using the same method. Three components were found at 644, 652 and 657 nm. The emission band of P650-655 included the last two components, which become predominant only in fully etiolated plants. Photoactive Pchlide with an emission maximum at 653 nm was detected in the light during development of leaves of photoperiodically grown plants.
Keywords: Darkness; listy rostlin; světlo; spektrofotometrie; Photoperiod; Spectrophotometry; fotoperioda; protochlorofylid; tma; fotobiologie; Plant Leaves; Light; Plants, Medicinal; Protochlorophyllide; léčivé rostliny; Photobiology; Fabaceae